The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0104170
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Findings of Sexual Intercourse Related Emergency Department Admissions: A First Overview

Abstract: ObjectivesSexuality is an essential aspect of human function, well-being and quality of life. Many people have sex without complications. However, there are some people who need to seek emergency medical help for related health problems. The aim of this study was to present a first overview of patients who received a radiological examination related to sexual intercourse based emergency department admission.MethodsOur centralized electronic patient record database was reviewed for patients who had been admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The frequency of HSA was 0.28% in 1 health checkup study [14] whereas 6.06% in 1 emergency service-based study of any sexual complication events [15], and ranged from 0.28% to 1.63% (average being 0.36%) in 5 clinic-based studies [16] Table 2). Frese et al [26] suggested the frequency of HSA to be 1% in their database but the total number of headache patients was unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of HSA was 0.28% in 1 health checkup study [14] whereas 6.06% in 1 emergency service-based study of any sexual complication events [15], and ranged from 0.28% to 1.63% (average being 0.36%) in 5 clinic-based studies [16] Table 2). Frese et al [26] suggested the frequency of HSA to be 1% in their database but the total number of headache patients was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…After an exclusion of duplications and studies from the same groups and data, there were a total of 97 publications eligible, including 1 community observational study [13], 1 health checkup study [14], 20 clinical case-series studies (more than 5 patients in index report) [15]- [34], and 75 case-report studies (1 to 5 patients in index report) ( Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Our case features sexual intercourse as a trigger of an acute intracerebral hemorrhage in a young female. Several studies have shown that sexual intercourse may provoke intracerebral hemorrhage, especially subarachnoid hemorrhage [ 3 , 4 ]. It has been reported that 14.5% of all subarachnoid hemorrhages are precipitated by sexual activity [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sexuality is an essential aspect of quality of life [ 1 – 3 ]. Nevertheless, sexual intercourse is physically challenging and leads to distinct changes in blood pressure, heart, and respiratory rate [ 3 , 4 ]; for an overview see Table 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation